Long-term graft occlusion in aortobifemoral position - Vasić Novak; Davidović Lazar; Marković Dragan; Sladojević Miloš (Vojnosanitetski Pregled)
Background/Aim. Aortobifemoral (AFF) bypass is still the most common surgical procedure used in treatment of aortoiliac occlusive disease. One of the most common complications of AFF bypass procedure is long-term graft occlusion. The aim of this study was to determine the cause of long-term graft occlusion in AFF position, as well as the results of early treatment of this complication. Methods. This retrospective study, performed at the Clinic of Vascular and Endovascular Surgery, Clinical Center of Serbia in Belgrade, involved 100 patients treated for long-term occlusion of bifurcated Dacron graft which was ensued at least one year after the primary surgical procedure. Results. The most common cause of the longterm graft occlusion was the process at the level of distal anastomosis or below it (Z = 3.8, p = 0.0001). End-to-end type of proximal anastomosis has been associated with a significantly increased rate of long-term graft occlusion (Z = 2.2, p = 0.0278). Five different procedures were used for the treatment of long-term graft occlusion: thrombectomy and distal anastomosis patch plasty (46% of the cases); thrombectomy and elongation (26% of the cases); thrombectomy and femoropopliteal bypass (24% of the cases); crossover bypass (2% of the cases) and a new AFF bypass (2% of the cases). The primary early graft patency was 87%. All 13 early occlusions occurred after the thrombectomy associated with patch plasty of distal anastomosis. Thrombectomy with distal anastomosis patch plasty showed a statistically highest percentage of failures in comparison to thrombectomy with graft elongation, or thrombectomy with femoro-popliteal bypass (Z = 2 984, p = 0.0028). Redo procedures were performed in all the cases of early occlusions. In a 30-day follow-up period after the secondary surgery, 90 (90%) patients had their limbs saved, and above knee amputation was made in 10 (10%) patients. Conclusion. Long-term AFF bypass patency can be obtained by proximal end-to-end anastomosis on the juxtarenal part of aorta and distal anastomosis on the bifurcation of the common femoral, or on the deep femoral artery. [Projekat Ministarstva nauke Republike Srbije, br. 175008]